The Effect of Leadership, Motivation, and Work Environment on Employee Performance at Bank Mandiri Smart Branch Duri Sudirman - Agustina, Wenny; Liswandi, Liswandi; Mujtahid, Iqbal Miftakhul (Journal Research of Social Science, Economics, and Management, 2025)
Bank Mandiri is the bank that receives the most customer complaints. Customer complaints reflect the suboptimal performance of employees in providing services, whether through digital channels or offline services at branch offices. This study aims to examine the influence of leadership style, motivation, and work environment on the performance of employees at Bank Mandiri Smart Branch Duri Sudirman. The research is quantitative descriptive in nature. Data collection techniques include questionnaires, observation, and documentation. The sample consisted of 119 bank employees. Data analysis was conducted using multiple regression. The results of the study indicate that motivation and work environment have a positive and significant effect on the performance of employees at Bank Mandiri Smart Branch Duri Sudirman, whereas leadership style does not have a positive and significant effect on employee performance at the branch.